Intraspecific variation in temperature dependence of gas exchange characteristics among Plantago asiatica ecotypes from different temperature regimes - Ishikawa, Kazumasa (The New phytologist, 2007)
There are large inter- and intraspecific differences in the temperature dependence of photosynthesis, but the physiological cause of the variation is poorly understood. Here, the temperature dependence of photosynthesis was examined in three ecotypes of Plantago asiatica transplanted from different latitudes, where the mean annual temperature varies between 7.5 and 16.8 degrees C. Plants were raised at 15 or 30 degrees C, and the CO(2) response of photosynthetic rates was determined at various temperatures. When plants were grown at 30 degrees C, no difference was found in the temperature dependence of photosynthesis among ecotypes. When plants were grown at 15 degrees C, ecotypes from a higher latitude maintained a relatively higher photosynthetic rate at low measurement temperatures. This difference was caused by a difference in the balance between the capacities of two processes, ribulose-1,5-bisphosphate regeneration (J(max)) and carboxylation (V(cmax)), which altered the limiting step of photosynthesis at low temperatures. The organization of photosynthetic proteins also varied among ecotypes. The ecotype from the highest latitude increased the J(max) : V(cmax) ratio with decreasing growth temperature, while that from the lowest latitude did not. It is concluded that nitrogen partitioning in the photosynthetic apparatus and its response to growth temperature were different among ecotypes, which caused an intraspecific variation in temperature dependence of photosynthesis